The reporting of the mode of transmission among HIV-positive men who have sex with men in Lviv oblast, Ukraine, 2014-2018 - Maryana Sluzhynska; Olga Denisiuk; Ruzanna Grigoryan; Yulia Sereda; Gennadiy Slabkiy; Olena Levytska; Volodymyr Vozniuk (Journal of Infection in Developing Countries)
Introduction: Men who have sex with men (MSM) are one of the key populations driving HIV/AIDS epidemic globally. To date, MSM is the only population in Ukraine where the prevalence and incidence of HIV is increasing. As HIV-positive MSM might feel uncomfortable to report homosexual intercourses as a possible mode of transmission (MoT) of HIV, they prefer being registered as patients with heterosexual or non-defined MoT. This study aimed to calculate the proportion of misclassified MoT among HIV-positive MSM registered in Lviv oblast, Ukraine, during 2014-2018.